Safety and efficacy of oral panobinostat plus chemotherapy in patients aged 65 years or younger with high-risk acute myeloid leukemia - DeAngelo, Daniel J.; Walker, Alison R.; Schlenk, Richard Friedrich; Sierra, Jorge; Medeiros, Bruno C.; Ocio, Enrique M.; Röllig, Christoph; Strickland, Stephen A.; Thol, Felicitas; Valera, Sue-zette; Dasgupta, Kohinoor; Berkowitz, Noah; et al. (Leukemia research, 2019)
The role of histone deacetylase inhibitors in the treatment of acute myeloid leukemia (AML) is not well characterized. The current study evaluated the safety and efficacy of panobinostat in combination with idarubicin and cytarabine in newly diagnosed patients aged ≤65 years with primary or secondary high-risk AML based on cytogenetic classification. Treatment included fixed dose idarubicin (12mg/m2/d, IV; day 1–3) and cytarabine (100mg/m2/d, continuous IV infusion; day 1–7) and escalating oral doses of panobinostat at 15mg, 20mg, and 25mg, thrice weekly starting at week 2 of a 28-day cycle. Forty-six patients were enrolled (primary AML [n=36], secondary AML [n=10]). The median age was 55 years. The most common all-grade AEs were diarrhea (54.3%), nausea (39.1%), vomiting, and decreased appetite (each, 21.7%), stomatitis (19.6%), and fatigue (17.4%). The overall response rate was 60.9%, 43.5% achieved a complete remission (CR), and 17.4% achieved CR with incomplete count recovery. The event-free survival at 1-year was 78.3%. Panobinostat in combination with idarubicin and cytarabine demonstrated tolerable safety and efficacy in younger patients with high-risk AML. The recommended phase 2 dose of panobinostat in this combination was 20mg. ClinicalTrials.gov registry no: NCT01242774, and European Trial Registry EudraCT no: 2009-016809-42.